Simplify this expression.

8.9 – 1.4x + (–6.5x) + 3.4

Answers

Answer 1
Answer:

Answer:

-7.9x+12.3

Step-by-step explanation:

8.9 – 1.4x + (–6.5x) + 3.4

8.9-1.4x-6.5x+3.4

8.9-7.9x+3.4

-7.9x+8.9+3.4

-7.9x+12.3


Related Questions

WILL MARK BRAINLIST!!!!Just need question 1 (i) and 2 (i), (ii)
Find EG (Line) Please Help :)I know the answer is 18, but I don’t know how it’s 18
Elena packed 48 cubes into this box each Cube has edges that are 1 centimeter how many layers of Cubes did Elena make
What is the exact area of a circle with a diameter of 25 pi m?A. 25 pi m²B. 50 pi m²C.156.25 pi m²D. 625 pi m²
How do you use the elimination method for this question? Please explain, because I really want to understand!

the graph of f(x) shown below has the same shape as the graph of g (x) = x^3 - x^2 but it is shifted to the left 1 unit what is the equation

Answers

Answer:

f(x) = (x + 1)³ - (x + 1)² = x³ + 2 x² + x

Step-by-step explanation:

To shift g(x) to the left by one unit, replace all x in the expression of g(x) with (x + 1). How does this work? For example, g(x) = -2 for x = -1 in this question. f(x) = g(x + 1) may also equate -2, but only one unit to the left of x = -1 at x = -2 since -2 + 1 = -1. So is the case for the rest of the points on g(x). f(x) = g(x + 1) leads to the same set of values but only at one unit to the left. Adding one to the independent variable of g(x) shifts the graph to the left by one unit.

To find g(x + 1), replace every x in the equation x³ - x² with (x + 1):

f(x) = g(x + 1) = (x + 1)³ - (x + 1)².

Expand (x + 1)³ - (x + 1)² using the binomial theorem:

f(x) =  (x + 1)³ - (x + 1)² = x³ + 3 x² + 3 x + 1 - (x² + 2 x + 1) = x³ + 2 x² + x

Answer:

f (x) = (x-1)^3 - (x-1)^2

Step-by-step explanation:

What percent of 96 is 26?

Answers

Multiply 26 by .96 and get 24.96

10) 4n^2 - 12n + 9 = 0​

Answers

Answer: n  =  −  3/2

Step-by-step explanation:

4n^2 - 12n + 9 = 0​     Factor using the perfect square rule.

(  2  n  +  3  )^  2  =  0

Set   2  n  +  3   equal to   0   and solve for   n.

n  =  −  3/2

The result can be shown in multiple forms.

Decimal Form:  n  =  −  1.5

Mixed Number Form:  n  =  −  1  1/2

What is y+6x=11; 3x+2y=-2?

Answers

The answer is y=5 and x=83.


ヽ(◉ ͜ʖ◉)ノ







y+6x=11; 3x+2y=-26x+y+6x=11+6x(Add -6x to both sides)
y=6x+11
Substitute6x+11foryin3x+2y=−2
3x+2y=−2
3x+2(6x+11)=2
9x+22=−2(Simplify both sides of the equation)
9x+22+−22=−2+−22(Add -22 to both sides)
9x=24
9x/−9=−24/−9(Divide both sides by -9)
x=8/3

For a school fund raising project, Aiden and Jacob collected money in the ratio of 3.5 : 6.8. Jacob collected $115.50 more than Aiden. Find the total amount of money they collected.

Answers

x - the amount of money collected by Aiden
y - the amount of money collected by Jacob

Aiden and Jacob collected money in the ratio of 3.5 : 6.8.
(x)/(y)=(3.5)/(6.8) \n6.8x=3.5y \nx=(3.5)/(6.8)y \n x=(35)/(68)y

Jacob collected $115.50 more than Aiden.
x+115.5=y \nx=y-115.5 \n \nx=x \n(35)/(68)y=y-115.5 \n(35)/(68)y-y=-115.5 \n(35)/(68)y-(68)/(68)y=-115.5 \n-(33)/(68)y=-115.5 \ny=-115.5 * (-(68)/(33)) \ny=238 \n \nx=y-115.5=238-115.5=122.5 \n \nx+y=238+122.5=360.5

The total amount of money they collected is $360.50.

PLEASE HELP I COULD REALLY REALLY USE IT

Answers

1. 10+24-:(7+1)
10+24-:(8)
10+3
13
2. 1+8*2-6
1+16-6
16-6
10
3.6(3+6)-5^2
6(3+6)-25
6(9)-25
54-25
29
4. (15-5)*2/5-1
10*2/5-1
20/5-1
20/4
5
5. 2*5+(1+2+6)x5
2*5+9*5
10+9*5
10+45
55
6. 4-(8-6)/2    +6+6
4-(2)/2 +6+6
2/2 +6+6
1+6+6
13



Hi. I took a glance at your paper and I say you should use PEMDAS. Follow that and this should be a lot easier. Or you just take the anwsers from above.